Male Infertility Contemporary Clinical Approaches, Andrology, ART & Antioxidants - Parekattil, Sijo J.; Agarwal, Ashok; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
A ground-breaking contribution to the literature, Male Infertility: Contemporary Clinical Approaches, Andrology, ART & Antioxidants offers a comprehensive review of well-established, current diagnostic and treatment techniques for male infertility. This state-of-the-art, evidence-based resource incorporates new multidisciplinary and complementary medicine approaches to create a first-of-its-kind guide to treatment strategies involving antioxidants for male infertility. Designed as an easily accessible practical reference for daily use, Male Infertility: Contemporary Clinical Approaches, Andrology, ART & Antioxidants provides a high quality guide for urologists, reproductive endocrinologists, embryologists, andrologists, biologists and research scientists interested in the role that antioxidants play in male infertility.
Causes of Male Infertility -- Laboratory Evaluation for Male Infertility -- Imaging Modalities in the Management of Male Infertility -- Endocrinopathies -- Molecular Mechanisms of Antioxidants in Male Infertility -- Surgical Treatment for Male Infertility -- Microsurgery for Male Infertility: The AIIMS Experience -- Advanced Techniques of Vasoepididymostomy -- Grafting Techniques for Vasectomy Reversal -- Mini-incision Vasectomy Reversal Using the No-Scalpel Vasectomy Instruments and Principles -- Robotic Microsurgery for Male Infertility and Chronic Orchialgia -- Robot-Assisted Vasectomy Reversal -- Robotic-Assisted Varicocelectomy -- Epidemiological Considerations in Male Infertility -- Male Infertility from the Developing Nation Perspective -- Ethical Dimensions of Urology: Four Case Studies -- Management of Fertility in Male Cancer Patients -- Genetic Aspects of Male Infertility -- Novel Approaches in the Management of Klinefelter's Syndrome -- ART and Its Impact on Male Infertility Management -- Fuel/Energy Sources of Spermatozoa -- Oxidative Stress -- Loss of Intracellular Antioxidant Enzyme Activity During Sperm Cryopreservation: Effects on Sperm Function After Thawing -- Varicocele -- Infection in Infertility -- Ejaculatory Dysfunction and Vasodynamics -- Environmental Factors -- Exogenous Medication or Substance-Induced Factors -- Sperm DNA Damage and Antioxidant Use: Roles in Male Fertility -- Common Male Infertility Disorders: Aging -- Apoptosis and Male Infertility -- Impact of Spinal Cord Injury -- Obesity and Male Fertility -- Nutritional Pathways to Protect Male Reproductive Health -- Natural Antioxidants -- Synthetic Antioxidants -- Antioxidant Therapy for the Enhancement of Male Reproductive Health: A Critical Review of the Literature -- In Vitro Studies of Antioxidants for Male Reproductive Health -- Micro- Testicular Sperm Extraction -- Sperm Processing and Selection -- Antioxidants in Sperm Cryopreservation -- Antioxidants in ICSI -- Antioxidants in IMSI -- Role of Sperm-Hyaluronic Acid Binding in the Evaluation and Treatment of Subfertile Men with ROS Affected Semen: Assessment of Sperm with Oxidative Damage and HA-Mediated ICSI Sperm Selection -- Extended Embryo Culture Supplementation -- Best Practice Guidelines for the Use of Antioxidants -- Harmful Effects of Antioxidant Therapy.
Keywords: Medicine; Obstetrics; Endocrinology; Reproductive Medicine; Urology; Cytology; Developmental biology; Medicine & Public Health; Urology/Andrology.; Endocrinology; Reproductive Medicine; Developmental Biology; Cell Biology; Obstetrics/Perinatology.